REPRESENTASI WACANA GENDER DALAM UNGKAPAN BERBAHASA INDONESIA DAN BAHASA INGGRIS: ANALISIS WACANA KRITIS - Budiwati, Tri Rina (Sekolah Pascasarjana UGM, 2011)
The result depicts that based on intra-linguistic analysis, English, and Indonesian idioms which contain gender discourse are in the forms of noun, phrases, Sub-clause, Simple sentence, Elliptical sentence, Compound, Complex, and Compound-Complex sentences. Based on the meaning and reference analysis, it is known that such idioms have various meanings: strength and weaknesses, success, marriage, sexuality, negative things, and wisdom. Besides, seen from the doer, the idioms can refer to men, women, and men and/or women. Based on CriticalDiscourse Analysis (CDA), such idioms can be analyzed based on the aspects of action, context, history, power, ideology and representation, which, then, are known that: (a) men are assumed as representative in various affairs and things (esp. in success and goodness); (b) men are active in marriage and sexuality; (c) women take more part in domestic domain; (d) women become negative metaphor; and (e) there is unequal relationship between womenand men.